PERANAN ELECTRONIC WORD OF MOUTH DALAM KEPUTUSAN BERKUNJUNG: Survey of domestic tourists visiting Kampung Karuhun, Kabupaten Sumedang - Nurhidayat, Wildan; Napu, Della Maghfira; Sukirman, Oman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
Sumedang is improving in optimizing the tourism sector. Several strategies are planned to make Sumedang Regency a new tourist destination. One of the leading tourist destinations in Sumedang is Kampung Karuhun. Karuhun Village offers a beautiful green mountain atmosphere with an eco green park concept so that tourists will be presented with very beautiful natural nuances. The fluctuating level of tourist visits makes managers have to design marketing strategies to influence the decision of potential tourists to visit. One of them is by utilizing information technology in the form of electronic word of mouth (e-WOM). This study aims to determine the effect of electronic word of mouth on the decision to visit tourists to Karuhun village, Sumedang. The type of research used was quantitative research with a descriptive approach and verification using multiple regression analysis techniques. The method used in this research was a survey method. The sample in this study were 210 respondents with a convenience sampling. The test results show that electronic word of mouth on the decision to visit has an effect simultaneously and partially. E-Wom has a positive influence on the decision to visit Kampung Karuhun.